Determination of mercury Using 4-Amino-3-Mercapto-1,2,4-Triazine(4H)-5-One as an Indirect Masking Reagent - Narayana, B.; Gajendragad, M.R. (Asian Journal of Chemistry, 2010)
A selective complexometric determination of mercury is proposed, 4-amino-3-mercapto-1,2,4-triazine (4H)-5-one being used as masking agent. Mercury(II) is first complexed with a known excess of EDTA and the surplus EDTA is back titrated (pH 5.0–6.0, hexamine) with lead nitrate solution using xylenol orange as indicator. 4-Amino-3-mercapto 1,2,4-triazine (4H)-5-one in acetone-water mixture is then added to displace EDTA from the Hg–EDTA complex and the released EDTA is titrated with lead nitrate solution. Reproducible and accurate results are obtained in the range 5–72 mg of mercury. The interference of various cations has been studied. The method also works for the analysis of mercury in its complexes.